Studying the Pharmagenomic effect of Portulaca oleracea extract on anti-diabetic therapy using the Collaborative Cross mice - Ruba Yehia; Iqbal M. Lone; Ibrahim Yehia; Fuad A. Iraqi (Elsevier, 2023)
Background: Portulaca oleracea L. (PO) is a herb widely used in folk medicine as antioxidant and mainly as an anti-diabetic. However, scientific evidence of its effects remains very limited. Here we aim to unravel the effect of the host genetic background on the PO treatment in the development of obesity and type 2 diabetes (T2D) using the genetically diverse Collaborative Cross (CC) mouse model, which could contribute to better understand and design personalized medical treatment. Results: We have studied the PO treatments efficacy on reduction of body weight (BW) and glucose tolerance ability in 221 mice of 13 different CC lines as a response to two different diets: the control match diet (CMD - 10% fat) as a control group and the high-fat diet (HFD - 60% fat) as the experiment group. Glucose tolerance ability was determined by a 180 minutes Intraperitoneal Glucose Tolerance Test (IPGTT) and the calculation of the area under the curve (AUC) was made. PO treatments started in week 12 of the dietary challenge and lasted for 4 weeks. PO was given to the mice every other day by intraperitoneal (IP) injection at concentration of 200mg/kg. The results showed significant sex effect across the different lines and assessed traits; therefore, male and female mice data was analyzed separately. Sex differences among lines were analyzed by ANOVA and shown to be significant (P <0.05) for BW and IPGTT-AUC in three time points: initial time point, after three months of dietary challenge and when PO treatment completed. Additionally, the results showed a significant increase in BW for both female and males maintained on HFD and CMD for 12 weeks period. Furthermore, significant increase in Total AUC values for both sexes maintained on HFD was showed while mice maintained on CMD did not develop any insulin resistance keeping their glucose levels slightly lower than the initial time point. Thenceforth, a four weeks of PO treatment showed a significant decrease in glucose levels in the HFD group, presenting that male mice were more sensitive to the treatment than females. Furthermore, PO treatment seemed to affect female mice fed with CMD rather than male mice maintained on the same diet. Conclusions: Our findings confirm the effect of PO treatment as an antidiabetic agent due to its significant effect in reducing glucose levels in CC mice that developed T2D induced by HFD. Additionally, a stabilizing effect on body weight as a response to PO treatment was shown. Variations among the different CC lines might be explained by differences in host genetics. Further studies can provide a base for a pharmacogenetics approach to treat T2D.